Training on Making Antiseptic Liquid Soap for Mangrove Type Pedada (Sonneratia cassiolaris) to the Community in Tani Baru Village, Anggana District, Kutai Kartanegara Regency, East Kalimantan Province - Uce Lestari; Miko Asih Soenarih; Galih Puja Satrio (CV. Media Digital Publikasi Indonesia, 2023)
One of the efforts to increase public awareness of the importance of preserving mangrove ecosystems in the Mahakam Delta is by developing the capacity of the community to be able to take advantage of the potential of existing mangroves in the Mahakam Delta region. When the community is able to obtain economic value from the utilization of non-timber mangrove forest products, it is hoped that public awareness of the existence and sustainability of mangrove forests will increase. One of the mangrove products that has economic value and is a daily need for the community is an antiseptic liquid soap with the addition of pedada (Sonneratia cassiolaris) mangrove fruit extract. Antiseptic liquid soap with pedada fruit extract can be utilized and meet the sanitation needs of the community in Tani Baru Village, Anggana District, Kutai Kartanegara Regency as one of the villages in the Mahakam Delta region in particular. With the training on making bacada fruit antiseptic liquid soap, the aim is for the community to be able to increase their creativity in exploring pedada-type mangroves into a product that provides added value and high economic value. The results that have been achieved in this training are that the community is able to make their own antiseptic liquid soap for their daily needs and can open up business opportunities in entrepreneurship